2023
DOI: 10.1002/jcpy.1370
|View full text |Cite
|
Sign up to set email alerts
|

Time moving or ego moving? How time metaphors influence perceived temporal distance

Abstract: Consumers often use spatial metaphors to describe time. Through six studies, the present research demonstrates that time metaphors influence consumers' perceptions of the temporal distance to future events. Specifically, an ego‐moving metaphor, which characterizes the movement of the self across a timeline from present to future, leads consumers to perceive a target event as more temporally distant than a time‐moving metaphor that illustrates the movement of the event from future to present. This time metaphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…Xu et al argue that ego-moving descriptions increase perceived temporal distance due to a reduction in psychological arousal when individuals conceptualise themselves approaching (rather than being approached by) future events. Supporting this argument, participants perceived a difficult job interview next week as more temporally distant when it was described using an ego-moving (vs. time-moving) metaphormediated by decreased psychological arousal [14,Study 2]. This finding is also consistent with the theoretical framework we have outlined, with an ego-moving perspective allowing people to maintain psychological distance from potentially threatening or aversive future events.…”
Section: Perceived Control and Perceived Temporal Distancesupporting
confidence: 66%
See 3 more Smart Citations
“…Xu et al argue that ego-moving descriptions increase perceived temporal distance due to a reduction in psychological arousal when individuals conceptualise themselves approaching (rather than being approached by) future events. Supporting this argument, participants perceived a difficult job interview next week as more temporally distant when it was described using an ego-moving (vs. time-moving) metaphormediated by decreased psychological arousal [14,Study 2]. This finding is also consistent with the theoretical framework we have outlined, with an ego-moving perspective allowing people to maintain psychological distance from potentially threatening or aversive future events.…”
Section: Perceived Control and Perceived Temporal Distancesupporting
confidence: 66%
“…Also of relevance to the present study, research by Xu et al [14] (published after data collection for the present study had concluded) appeared to demonstrate that future events described using ego-moving (vs. time-moving) linguistic metaphors were perceived as more temporally distant, regardless of valence. Xu et al argue that ego-moving descriptions increase perceived temporal distance due to a reduction in psychological arousal when individuals conceptualise themselves approaching (rather than being approached by) future events.…”
Section: Perceived Control and Perceived Temporal Distancesupporting
confidence: 64%
See 2 more Smart Citations
“…For example, the understanding of the novel metaphor "negotiation is a muscle" is predicated on their shared attribute, that is, both can be perfected through practice (Jamrozik et al, 2016). Recall that the ego-moving representation puts a longer distance between the ego and the future event (i.e., choosing the deferral of the meeting to next "Friday" over the advancement of the meeting to next "Monday" when decoding the ambiguous meeting question) and as a result latest research found that adoption of the ego-moving perspective engendered a higher level of consumer impatience in a waiting situation (Xu et al, 2023). This insight, in combination with the linguistic illustrations that use spicy substitutes to indicate temporal urgency suggests that the spicy-ego-moving metaphor link may be founded on a relational affinity of keenness for action, whereby spicy-evoked temporal urgency and the resultant eagerness to move would activate the same psychological state and spatial motivation implicated in the ego-moving representation.…”
Section: Justificationsmentioning
confidence: 99%